Dynamic QTL mapping for plant height in the hybrid population of Agropyron Gaertn. (12th March 2020) - Che, Yonghe; Song, Nan; Yang, Yanping; Yang, Xinming; Zhang, Yan; Zhang, Jinpeng; Han, Haiming; Li, Xiuquan; Zhou, Shenghui; Li, Lihui; Liu, Weihua
Abstract: Plant height (PH) plays a very important role for plant breeding and also serves as a model trait to dynamic development study. The dynamic quantitative trait locus (QTL) analysis for PH of Agropyron Gaertn. was carried out in a cross‐pollination (CP) hybrid population of A. Gaertn. based on the phenotypic data of PH at different developmental stages in four year‐sites and the constructed single‐nucleotide polymorphism (SNP) genetic map. The results showed that 69 QTL and nine major QTL were detected by unconditional QTL mapping. A total of 107 QTL and 13 major QTL were found using conditional QTL mapping. Forty‐seven QTL were detected by two methods. Two unconditional QTL, Qph2‐5 and Qph3‐4, were expressed as major and stable QTL for PH. Four major stable conditional QTL for PH, cQph4‐1, cQph4‐8, cQph6‐2 and cQph6‐7, were detected. Two conditional PH QTL, cQph3‐5 and cQPh3‐7, were identified in four environments over multiple stages. The gene/QTL controlling PH was expressed in a certain spatiotemporal manner. These results could also provide a reference for genetic and breeding research of related plant.